1993
DOI: 10.1021/bi00210a019
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of the sugar chains of human leukocyte common antigen CD45

Abstract: The leukocyte cell surface glycoprotein CD45 is a protein tyrosine phosphatase and is involved in signal transduction mediated by the T cell antigen receptor. The asparagine-linked sugar chains were released as oligosaccharides from purified CD45 by hydrazinolysis. Approximately 6 mol of sugar chains was released from 1 mol of CD45. These sugar chains were converted to radioactive oligosaccharides by reduction with NaB3H4 and separated into neutral and acidic fractions by paper electrophoresis. All of the acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 51 publications
1
31
1
Order By: Relevance
“…3C). In this case, galectin-1 may bind to other CD45 glycans that bear the lactosamine sequences (13,34,52,53). However, the interaction of 35 stromal cell galectin-1 with CD45 on T cells appeared markedly reduced on BW5147 cells lacking the C2GnT (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…3C). In this case, galectin-1 may bind to other CD45 glycans that bear the lactosamine sequences (13,34,52,53). However, the interaction of 35 stromal cell galectin-1 with CD45 on T cells appeared markedly reduced on BW5147 cells lacking the C2GnT (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been reported that CD45 expressed on T and B cells is a major protein that reacts with anti-i and anti-I antibodies (28,29) and contains mainly bi-, tri-, and tetraantennary complex-type sugar chains. Tetraantennary complex-type N-glycan (30) and O-glycan (28, 31) on CD45 possess polylactosamine. We investigated the glycans on CD45 molecules by lectin microarray analysis (data not shown) and found LEL signals on anti-CD45 mAb immunoprecipitates from WT leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Kishihara, K., Penninger, J., Wallace, V. A., Kundig, T. M., Kawai, to the multiply sialylated complex-type than the mono-sialylated K., Wakeham, A., Timms, E., Pfeffer, K., Ohashi, P. S., Thomas, oligosaccharides [31]. complex-type with and without poly(N-acetyllactosamine) [28]. by the electrophoretic mobility of them, and may not interact …”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of the N-linked sugar chains of CD45 from human peripheral blood leukocytes revealed that they are membrane and cytoplasmic domains [17Ϫ19]. The individual isoforms showed differences in the interaction with CD4-T-cell mostly of complex-type with highly branched tri-and tetra-antennary structures and poly(N-acetyllactosamine) units [28]. antigen receptor-complex [20] and in the activation of intracellular signals [21Ϫ24].…”
mentioning
confidence: 99%